Awareness of predatory journals and open access among medical oncologists: results of an online survey - Richtig, Georg; Richtig, Erika; Böhm, Alexandra; Oing, Christoph; Bozorgmehr, Farastuk; Kruger, Stephan; Kiesewetter, Barbara; Zielinski, Christoph; Berghoff, Anna S. (ESMO open, 2019)
Introduction Predatory journals harm the integrity of science as principles of ‘good scientific practice’ are bypassed by omitting a proper peer-review process. Therefore, we aimed to explore the awareness of predatory journals among oncologists. - Methods An online survey among oncologists working in Germany or Austria of various professional surroundings was conducted between October 2018 and April 2019. - Results One hundred and eighty-eight participants (55 women (29.2%), 128 men (68.1%)) completed the questionnaire. 41 (21.8%) participants indicated to work in a hospital, 24 (12.8%) in private practice and 112 (59.6%) in a university hospital. 98.9% of participants indicated to actively read scientific articles and consider them in clinical decision-making (96.3%). 90.4% of participants indicated to have scientific experience by publishing papers in journals with peer-review system. The open-access system was known by 170 (90.4%), predatory journals by 131 (69.7%) and Beall’s list by 52 participants (27.7%). Predatory journals were more likely to be known by participants with a higher number of publications (p<0.001), with more high-impact publications (p=0.005) and with recent publications (p<0.001). Awareness of predatory journals did not correlate with gender (p=0.515) or translation of scientific literature into clinical practice (p=0.543). - Conclusions The problematic topic of ‘predatory journals’ is still unknown by a considerable amount of oncologist, although the survey was taken in a cohort of oncologists with scientific experience. Dedicated educational initiatives are needed to raise awareness of this problem and to aid in the identification of predatory journals for the scientific oncology community.
Gesehen am 06.04.2020